1996
DOI: 10.1159/000174041
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Pattern of Sodium Excretion in Dogs with and without Chronically Reduced Renal Perfusion Pressure

Abstract: In 5 conscious dogs the diurnal patterns of urinary sodium excretion (UNaV) were investigated, initially during 1 control day and, thereafter, during 4 days of servo-controlled reduction of renal perfusion pressure (rRPP). The individual dog’s mean arterial blood pressure was reduced to 80% of the blood pressure on the control day. This value was always found to be below the threshold for the pressure-dependent renin release. During the entire study period urine was collected in 4-hour intervals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
(23 reference statements)
0
6
1
Order By: Relevance
“…Our results document clear rhythmicity of heart rate, blood pressure, and rectal temperature in dogs and demonstrate that the rhythmicity is independent of the feeding schedule. These results are in contrast with those of numerous studies that failed to detect daily rhythmicity in dogs (Hawking et al., 1971; Marvin and Reese, 1986; Gobello et al., 2001, 2002; Koyama et al., 2003) or failed to demonstrate rhythmicity in the absence of an experimenter‐imposed cycle of feeding (Rawson et al., 1965; Corea et al., 1996; Liesegang et al., 1999; Mishina et al., 1999; Matsunaga et al., 2001; Miyazaki et al., 2002). On the other hand, our results are in agreement with a limited number of studies on dogs in which daily rhythmicity was unequivocally demonstrated in heart rate (Ashkar, 1979; Olsson et al., 2003), locomotor activity (Nishino et al., 1997; Siwak et al., 2003), and urinary excretion (Uechi et al., 1994).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results document clear rhythmicity of heart rate, blood pressure, and rectal temperature in dogs and demonstrate that the rhythmicity is independent of the feeding schedule. These results are in contrast with those of numerous studies that failed to detect daily rhythmicity in dogs (Hawking et al., 1971; Marvin and Reese, 1986; Gobello et al., 2001, 2002; Koyama et al., 2003) or failed to demonstrate rhythmicity in the absence of an experimenter‐imposed cycle of feeding (Rawson et al., 1965; Corea et al., 1996; Liesegang et al., 1999; Mishina et al., 1999; Matsunaga et al., 2001; Miyazaki et al., 2002). On the other hand, our results are in agreement with a limited number of studies on dogs in which daily rhythmicity was unequivocally demonstrated in heart rate (Ashkar, 1979; Olsson et al., 2003), locomotor activity (Nishino et al., 1997; Siwak et al., 2003), and urinary excretion (Uechi et al., 1994).…”
Section: Discussioncontrasting
confidence: 99%
“…Numerous investigators failed to detect daily rhythmicity in body temperature (Hawking et al., 1971; Marvin and Reese, 1986) or in the secretion of various hormones, including prolactin (Gobello et al., 2001), cortisol (Koyama et al., 2003), and growth hormone (Gobello et al., 2002). In other instances, rhythmicity was detected in body temperature (Rawson et al., 1965; Miyazaki et al., 2002), cardiovascular parameters (Mishina et al., 1999; Matsunaga et al., 2001; Miyazaki et al., 2002), and other functions (Corea et al., 1996; Liesegang et al., 1999) but the rhythmicity seemed to reflect merely an exogenous effect of feeding rather than an endogenous rhythmic process. While it is possible that canine physiology is unique in its lack of endogenous rhythmicity, it is also possible that studies conducted on dogs have lacked the experimental rigour necessary for the identification of rhythmicity.…”
Section: Introductionmentioning
confidence: 97%
“…Post‐prandial excretion of organic phosphates is increased for about 8 hours then diminishes markedly thereafter 13 . Sodium excretion in five dogs, fed their daily high sodium ration at 0830 h, was found to peak 4 to 8 hours after feeding and decrease to low values at night, 12 to 15 hours post‐prandially 14 . It is expected that post‐prandial excretion of excess dietary electrolytes that normally occupy the extracellular fluid space will have occurred well within 15 hours, however specific data is not available for electrolytes other than sodium and phosphate 15 .…”
Section: Discussionmentioning
confidence: 99%
“…While ‘pressure natriuresis’ has been assumed to be a major controller of Na + excretion in long‐term as well as acute control (Guyton, 1990 a , 1991; Cowley, 1992; Hall et al 1996), it is also well known that renal Na + excretion may change many‐fold without arterial pressure changes. For instance, the diurnal changes in Na + excretion due to intermittent Na + intake occur unrelated to changes in arterial pressure, and spontaneous RPP fluctuations do not change Na + excretion (Palm et al 1992; Corea et al 1996; Reinhardt et al 1996). As outlined in the introduction, previous studies that attempted to assess the role of pressure natriuresis in relation to short‐term control of TBS with acute i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Clearances Clearance of exogenous creatinine was used to assess the glomerular filtration rate (GFR), and lithium clearance used for calculation of proximal tubular reabsorption rate via fractional lithium excretion (FELi). As described by Corea et al (1996), a priming dose of lithium (3 mmol Li 2 CO 2 ; Quilonium retard oblong, SKD, Giessen, Germany) was fed 48 and 24 h prior of the experiment. An oral creatinine bolus of 50 ml creatinine 2% was given 60 min before starting the running‐in time.…”
mentioning
confidence: 99%